Development of Bi-functional Graphene Based Catalyst for Biodiesel Production from Microalgae Oil - LOY CHUN MINH, ADRIAN (IRC, 2017)
In this study, a high novelty bi-functional catalyst silicon carbide/sodium hydroxide-graphene oxide (Sic/NaOH-GO) was successfully developed and characterized using Fourier transform infrared spectroscopy (F-TIR), Thermogravimetric analysis (TGA/DTA), N2 adsorption (BET), Scanning electron microscope (SEM), and X-ray diffraction (XRD). The catalyst was applied on microalgae lipid that contains 26 % of free fatty acid (FFA) for biodiesel production under microwave irradiation. The effect of different reaction parameters such as catalyst loading, methanol to oil ratio, reaction temperature and reaction time were studied to optimize the reaction conditions. It was found that the optimum reaction conditions to attain 80.4 % of fatty acid methyl ester (FAME) content was methanol to oil molar ratio of 48, reaction time 5 min, amount of catalyst 4 wt % and reaction temperature 85 ˚C. Apart from that, a kinetic model was developed for the transesterification reaction under microwave irradiation. The attained activation energy of the developed bi-functional catalyst was 30 KJ/mol, which was comparable to other heterogeneous and homogeneous reported in literature.